Eocene Sedimentary–Diagenetic Environment Analysis of the Pingtai Area of the Qaidam Basin - Guoqiang Sun; Shuncun Zhang; Yetong Wang; Yaoliang Li; Hui Guo; Shangshang Bo (Applied Sciences, 2022)
Based on the petrological characteristics and elemental geochemical analysis of core samples from the Pingtai area in the northern structural belt of the Qaidam Basin, this study shows that the clay mineral assemblage of Lulehe Formation sandstone is dominated by high contents of smectite, chlorite and illite, and does not contain illite–smectite mixed layers or kaolinite. The chlorite and illite in the Xiaganchaigou Formation decreased gradually and the smectite disappeared. In addition, illite–smectite mixed layers began to appear and kaolinite was not present. These results indicate that the diagenetic environment of the Pingtai area in the early Eocene was dominated by alkaline media poor in K+ and rich in Mg2+, Na+ and Ca2+. In the late Eocene, K+ content in the diagenetic medium increased significantly, and smectite began to transform into illite. From the early Eocene to the late Eocene, the overall climate and environmental characteristics showed a transition from cold and dry to a cold climate that alternated between dry and wet. The content changes of common oxides, such as CaO, MgO, K2O, Na2O, SiO2, Al2O3, Fe2O3 and TiO2, showed obvious correlation. Based on the content and ratio change tendencies of Sr, Ba, Cu, Zn, U, Th, Ce and other trace elements, combined with the variation characteristics of rare earth element contents, it is suggested that the Lulehe Formation was dominated by a dry and cold freshwater sedimentary environment, and that paleoclimatic conditions were relatively cold and arid during this sedimentary period. However, the climate in the sedimentary period of the Xiaganchaigou Formation was dominated by a cold environment alternating between dry and wet, which also reflected the finding that the global climate was mainly cold and dry in the early Eocene and gradually became warm and humid in the late Eocene.